Psychometric attributes of WHOQOL-BREF among tuberculosis patients: Rasch model analysis - Sofiana, Liena; Adi, Mateus Sakundarno; Martini, Martini; Raharjo, Mursid (International Journal of Public Health Science (IJPHS), 2023)
The World Health Organization quality of life-BREF (WHOQOL-BREF) instrument has been used to assess several diseases, including chronic pain sufferers' quality of life. In Indonesia it can be utilized for evaluating the quality of life among tuberculosis (TBC) patients. This study aimed to assess the psychometric attributes of quality of life questionnaires among 123 respondents with TBC (56.9% males, 43.1% females) in Yogyakarta. This study employed the Rasch analysis technique for psychometric analysis. The findings indicate that six questions are biased in favour of the respondent's qualities. Four items do not statistically match an MNSQ (Mean-square or Standardized fit statistics) output value of >1.5 but are still acceptable (Pt. Meas Corr 0.3-0.8). Between the elements Q14-Q12 and Q12-Q21, there is a gap The responders' ability level is higher than the average problem difficulty level. The WHOQOL-BREF instrument revealed unidimensionality, and the evaluation scale worked properly when it was used with TBC patients with Cronbach's α value of 0.89. The WHOQOL-BREF scale continues to be appropriate for evaluating the patient quality of life since it has solid psychometric qualities.